High strength galvannealed steel sheet and method for producing the same
The development of a high-strength alloyed hot-dip galvanized steel sheet with a specific composition and microstructure addresses the challenges of achieving high strength and LME crack resistance, ensuring enhanced safety and performance in vehicle body structures.
Patent Information
- Application Number
- JP2021142112
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-26
- Filing Date
- 2021-09-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-09-01
AI Technical Summary
Existing high-strength steel sheets used in vehicle body structures face challenges in achieving high tensile strength, yield strength, and resistance to liquid metal embrittlement (LME) cracking, especially in complex welding scenarios and high-strength materials above 1150 MPa.
A high-strength alloyed hot-dip galvanized steel sheet with a specific chemical composition and microstructure is developed, including a base steel sheet with a martensite-dominated microstructure and a plating layer that undergoes an alloying treatment, achieving a yield strength of 970 MPa or more and a tensile strength of 1470 MPa or more, while providing excellent LME crack resistance.
The solution effectively achieves high yield and tensile strengths while maintaining excellent LME crack resistance, even in complex welding scenarios, thereby enhancing the safety and performance of vehicle body structures.
Smart Images

Figure 0007654510000005 
Figure 0007654510000006 
Figure 0007654510000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength galvannealed steel sheet having a galvannealed layer on the surface of a high-strength cold-rolled steel sheet, and a method for producing the same. [Background technology]
[0002] Steel sheets used in automobile body structural members are required to have high impact absorption energy from the viewpoint of collision safety.
[0003] Here, in steel plates, the tensile strength (TS) is high and the 0.2% yield strength σ 0.2 It is known that the higher the upper yield point UYP (Upper Yield Point), the higher the impact energy absorption of the steel plate. In the following, the tensile strength TS of the steel plate is simply referred to as "tensile strength" and the 0.2% yield strength σ 0.2 The upper yield point UYP is collectively referred to as "yield strength."
[0004] Therefore, steel sheets used in automobile body structural members are required to have high tensile strength and high yield strength. To meet the demand for high tensile strength and yield strength for steel sheets, the composition of steel sheets is becoming higher, that is, the content of additive elements in steel sheets is increasing. Such an increase in the content of additive elements is also occurring in base steel sheets used for galvanized steel sheets.
[0005] However, as the composition of steel sheets becomes higher, the occurrence of Liquid Metal Embrittlement (LME) cracking at the welded parts of steel sheets has become a problem. When galvanized steel sheets are welded, the heat applied to the galvanized steel sheets melts the zinc in the coating layer, and the molten zinc penetrates the grain boundaries of the base steel sheets at the welded parts. When tensile stress is applied due to thermal contraction after welding, cracks occur. Hereinafter, cracks that occur in this way are referred to as "LME cracking."
[0006] Therefore, currently, steel sheets used in automotive body structural members are required to have high tensile strength, high yield strength, and excellent LME cracking resistance.
[0007] Of these required properties, with regard to tensile strength, for example, Patent Document 1 describes a steel structure that has an area ratio of 80% or more of autotempered martensite, with less than 5% ferrite, 10% or less bainite, and 5% or less retained austenite, and the average number of precipitated iron-based carbides of 5 nm or more and 0.5 μm or less in the autotempered martensite is 1 mm 2 5 x 10 per 4 Patent Document 2 discloses a high-strength steel plate having martensite of 93 volume % or more, ferrite, pearlite and bainite of 2 volume % or less in total, retained austenite of 7 volume % or less, and in an image of the metallographic structure observed with a scanning electron microscope, the number of laths in martensite measured by a cut method over a total length of 300 μm is 240 or more, and the tensile strength is 1470 MPa or more.
[0008] As for LME cracking, Patent Document 3 describes a resistance spot welding method capable of suppressing the occurrence of LME cracking, in which three welding pulses are used in one spot welding plan, a first welding pulse and a second welding pulse are used to generate a nugget and suppress the occurrence of liquid metal embrittlement cracking, and the first welding pulse is a 3.75T diameter welding pulse. 1 / 2 ~4.25T 1 / 2 (wherein T represents the thickness of the steel sheet), the second welding pulse slowly grows the nugget, and a third welding pulse, which is a tempering pulse, is used to improve the plasticity of the weld spot. Patent Document 4 proposes a technology for obtaining excellent LME resistance by making the thickness of the surface softened portion of the steel sheet 5 μm or more. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 5365216 [Patent Document 2] JP 2019-173156 A [Patent Document 3] Special Publication No. 2019-536631 [Patent Document 4] Patent No. 6787535 Summary of the Invention [Problem to be solved by the invention]
[0010] However, Patent Documents 1 and 2 only consider the workability or yield strength in addition to the tensile strength of the steel sheet, and do not consider the LME cracking resistance.
[0011] In addition, the spot welding method proposed in Patent Document 3 does not take into consideration cases where various plate combinations including three or more steel plates are welded, or cases where disturbance conditions are applied during welding, and in such cases, there is a risk that the occurrence of LME cracking cannot be suppressed. In the technology disclosed in Patent Document 4, the tensile strength of the obtained steel plate is merely less than 1150 MPa, and Patent Document 4 does not take into consideration measures against the LME cracking resistance of high-strength materials of 1150 MPa or more.
[0012] The present invention has been made in consideration of the above problems, and has an object to provide a high-strength galvannealed steel sheet having a yield strength of 970 MPa or more, a tensile strength of 1470 MPa or more, and excellent LME cracking resistance, and a method for manufacturing such a high-strength galvannealed steel sheet. [Means for solving the problem]
[0013] As a result of extensive investigations, the present inventors have found that the above object can be achieved by the following invention.
[0014] A high-strength galvannealed steel sheet according to one aspect of the present invention is a high-strength galvannealed steel sheet having a plating layer on a surface of a base steel sheet, The base steel sheet is composed of: C: 0.19-0.30%, Si: more than 0%, less than 0.70%, Mn: 1.8-3.0%, P: more than 0%, less than 0.020%, S: more than 0%, less than 0.05%, Al: 0.015-0.060%, Cr: 0.05~0.8%, Ti: 0.015 to 0.080%, B: 0.0010~0.0150%, Mo: more than 0%, less than 0.40%, N: 0.0100% or less, and O: 0.0030% or less, and the remainder being iron and unavoidable impurities, The Cr content [Cr] (mass%) and the Si content [Si] (mass%) of the base steel sheet satisfy 2 × [Cr] - [Si] ≧ 0.1, In the metal structure of the base steel sheet, martensite (including tempered martensite and self-tempered martensite) is 82 vol% or more, ferrite, pearlite and bainite are 13 vol% or less, and retained austenite is 5 vol% or less, In an image of the metal structure of the base steel sheet observed with a scanning electron microscope, the number of laths in a total length of 300 μm measured by a cutting method is 200 or more, the yield strength is 970 MPa or more, and the tensile strength is 1470 MPa or more.
[0015] A method for producing a high-strength galvannealed steel sheet according to another aspect of the present invention comprises hot rolling a slab having the above composition, The hot-rolled steel sheet obtained by hot rolling is coiled at 620°C or higher, The coiled hot-rolled steel sheet is unwound and cold-rolled; The cold-rolled steel sheet obtained by cold rolling is heated and held in a temperature range of Ac3 point or higher for 11 s or more, and the heated and held cold-rolled steel sheet is cooled to a temperature range of 540 to 580 ° C. at an average cooling rate of 3 ° C. / s or more, and further cooled to a temperature range of 410 to 480 ° C. within 90 s, The cold-rolled steel sheet is cooled to obtain a base steel sheet, which is then subjected to hot-dip galvanizing. The hot-dip galvanized steel sheet obtained by hot-dip galvanizing is heated to a temperature range of 550°C or less to perform an alloying treatment of the hot-dip galvanizing, The method includes cooling the galvannealed steel sheet obtained by subjecting the hot-dip galvannealed steel sheet to an alloying treatment to a temperature range of 230 to 340° C. at an average cooling rate of 5° C. / s or more. Effect of the Invention
[0016] According to the present invention, it is possible to provide a high-strength galvannealed steel sheet having a yield strength of 970 MPa or more, a tensile strength of 1470 MPa or more, and excellent LME cracking resistance, and also to provide a method for manufacturing such a high-strength galvannealed steel sheet. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic diagram of a heat pattern of an annealing step according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an example of a scanning electron microscope photograph of the cross section of a test piece. [Diagram 3] FIG. 3 is a schematic diagram showing the state in which the number of laths is measured by the cutting method. [Figure 4] FIG. 4 is a front view of a sample for evaluating LME crack resistance. [Diagram 5] Figure 5 shows an example of an optical microscope photograph of a sample for observing LME cracks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, a high-strength galvannealed steel sheet according to one embodiment of the present invention will be described.
[0019] The high-strength galvannealed steel sheet according to the present embodiment is a high-strength galvannealed steel sheet having a plating layer on a surface of a base steel sheet. Each component of the high-strength galvannealed steel sheet will be described below.
[0020] (Base steel sheet) The base steel sheet of the high-strength galvannealed steel sheet according to this embodiment has the following chemical composition. In the following description of the chemical composition, "%" means "mass %". Hereinafter, the base steel sheet and the high-strength galvannealed steel sheet are collectively referred to simply as "steel sheet". The tensile strength TS of the steel sheet is also referred to simply as "tensile strength", and the 0.2% proof stress σ 0.2 The upper yield point UYP is also collectively referred to as "yield strength." Tensile strength and yield strength are also collectively referred to simply as "strength."
[0021] (C: 0.19~0.30%) C is an element necessary for ensuring the strength of the steel sheet. If the C content is insufficient, the tensile strength of the steel sheet decreases. In order to ensure sufficient strength of the steel sheet, the C content is set to 0.19% or more. The lower limit of the C content is preferably 0.20% or more, and more preferably 0.21% or more. However, if the C content is excessive, the volume fraction of the retained austenite becomes excessive, which may lead to a decrease in the yield strength of the steel sheet. Therefore, the C content is set to 0.30% or less. The upper limit of the C content is preferably 0.290% or less, more preferably 0.280% or less, even more preferably 0.270% or less, and even more preferably 0.260% or less.
[0022] (Si: more than 0%, less than 0.70%) Si is one of the important elements in the present invention. Si is known as a solid solution strengthening element, and is an element that effectively acts to improve the tensile strength while suppressing the decrease in ductility of the steel sheet. In addition, Si is also an element that has the effect of increasing the temper softening resistance of the martensite structure. In order to effectively exert these effects, the Si content is set to an amount exceeding 0%. The lower limit of the Si content is preferably 0.06% or more. More preferably, it is 0.07% or more, and even more preferably, it is 0.08% or more. However, if the Si content is excessive, the volume fraction of the retained austenite becomes excessive, which may lead to a decrease in the yield strength of the steel sheet. Furthermore, if the Si content is excessive, it may deteriorate the LME cracking resistance of the steel sheet. Therefore, the Si content is set to 0.70% or less. The upper limit of the Si content is preferably 0.60% or less, and more preferably 0.50% or less.
[0023] (Mn: 1.8-3.0%) Mn is an element that contributes to increasing the strength of steel sheets. To effectively exert such effects, the Mn content is set to 1.8% or more. The lower limit of the Mn content is preferably 1.9% or more, and more preferably 2.0% or more. However, an excessive Mn content may cause slab breakage, an increase in cold rolling load, and the like. Therefore, the Mn content is set to 3.0% or less. The upper limit of the Mn content is preferably 2.9% or less, and more preferably 2.8% or less.
[0024] (P: more than 0%, less than 0.020%) P is an element that is inevitably contained in steel, and it segregates at the grain boundaries of steel to promote grain boundary embrittlement. In order to avoid breakage during processing of the steel sheet, it is preferable to reduce the P content as much as possible. Therefore, the P content is set to 0.020% or less. The upper limit of the P content is preferably 0.015% or less, and more preferably 0.012% or less. As mentioned above, P is an impurity that is inevitably mixed into steel, and it is impossible to reduce the content to 0% in industrial production.
[0025] (S: more than 0%, less than 0.05%) Like P, S is an element that is inevitably contained in steel. S forms inclusions together with other elements in steel. These inclusions may cause breakage or the like of the steel sheet during processing. In order to avoid such breakage or the like of the steel sheet, it is preferable to reduce the S content as much as possible. Therefore, the S content is set to 0.05% or less. The upper limit of the S content is preferably 0.04% or less, and more preferably 0.03% or less. Note that, like P, it is impossible to reduce the S content to 0% in industrial production.
[0026] (Al: 0.015~0.060%) Al is an element that acts as a deoxidizer in steel. To effectively exert this function, the Al content is set to 0.015% or more. The lower limit of the Al content is preferably 0.025% or more, and more preferably 0.030% or more. However, if the Al content is excessive, a large amount of inclusions such as alumina are generated in the steel sheet, which may cause breakage during processing of the steel sheet. Therefore, the Al content is set to 0.060% or less. The upper limit of the Al content is preferably 0.055% or less, and more preferably 0.050% or less.
[0027] (Cr: 0.05~0.8%) Cr is one of the important elements in the present invention. Cr is an element that contributes to increasing the strength of steel sheets. Specifically, Cr is an element that improves the hardenability of steel sheets, reduces the amount of bainite generated during hardening, increases the number of martensite laths, and effectively acts to increase the strength of steel sheets. Furthermore, Cr is an element that does not easily deteriorate LME cracking resistance even if the content is increased. In order to effectively exert these effects, the Cr content is set to 0.05% or more. The lower limit of the Cr content is preferably 0.1% or more. However, if the Cr content is excessive, it may cause uncoated areas in hot-dip galvanized steel sheets and alloyed hot-dip galvanized steel sheets. Therefore, the Cr content is set to 0.8% or less. The upper limit of the Cr content is preferably 0.7% or less, more preferably 0.6% or less.
[0028] (Ti: 0.015~0.080%) Ti is an element that forms carbides and nitrides to improve the strength of the steel sheet. In addition, Ti is also an effective element for effectively exerting the hardenability improving effect of B described later. That is, Ti reduces N in the steel by forming nitrides. As a result, the formation of B nitrides is suppressed, B is in a solid solution state, and the hardenability improving effect of B can be effectively exerted. In this way, Ti contributes to increasing the strength of the steel sheet by improving the hardenability of the steel sheet by B. In order to effectively exert such effects, the Ti content is set to 0.015% or more. The lower limit of the Ti content is preferably 0.018% or more, and more preferably 0.020% or more. However, if the Ti content is excessive, Ti carbides and Ti nitrides become excessive, which may cause cracks during processing of the steel sheet. Therefore, the Ti content is set to 0.080% or less. The upper limit of the Ti content is preferably 0.070% or less, and more preferably 0.060% or less.
[0029] (B: 0.0010~0.0150%) B is an element that improves hardenability and contributes to increasing the strength of steel sheet. To effectively exert such an effect, the B content is set to 0.0010% or more. The lower limit of the B content is preferably 0.0012% or more, and more preferably 0.0014% or more. However, if the B content is excessive, the effect becomes saturated and the cost only increases. Therefore, the B content is set to 0.0150% or less. The upper limit of the B content is preferably 0.0140% or less.
[0030] (Mo: more than 0%, less than 0.40%) Mo is an element that contributes to increasing the strength of steel sheets. The effect increases as the Mo content increases. To effectively exert this effect, the Mo content is set to more than 0%. The lower limit of the Mo content is preferably 0.10% or more, and more preferably 0.20% or more. However, if the Mo content is excessive, the effect saturates and the cost increases. Therefore, the Mo content is set to 0.40%. The upper limit of the Mo content is preferably 0.30% or less.
[0031] (Relationship between Si content and Cr content) The Cr content and Si content of the base steel sheet of the high-strength galvannealed steel sheet according to this embodiment satisfy the following formula (1). By satisfying formula (1), the hardenability of the high-strength galvannealed steel sheet can be improved. By improving the hardenability, the amounts of ferrite and bainite produced during quenching can be limited. Furthermore, by satisfying formula (1), the balance between the Si content and the Cr content becomes appropriate, making it possible to reduce the occurrence of LME cracking in the region around the weld. In other words, it is possible to achieve both high strength and excellent LME cracking resistance in the high-strength galvannealed steel sheet. 2 × [Cr]-[Si]≧0.1 … (1) In formula (1), the [element symbol] represents the content (mass%) of the corresponding element in the base steel sheet.
[0032] (remainder) The basic components of the base steel sheet of the high-strength galvannealed steel sheet according to this embodiment are as described above, with the balance being substantially iron. However, it is naturally acceptable that impurities inevitably introduced into the steel due to the conditions of raw materials, materials, manufacturing equipment, etc. are contained in the steel. That is, the balance of the basic components of the base steel sheet consists of iron and inevitable impurities. In addition to the above-mentioned P and S, such inevitable impurities include, for example, N and O. It is preferable that N and O are within the following ranges, respectively.
[0033] (N:0.0100% or less) N is an impurity element that is inevitably contained in steel. If the N content is excessive, there is a risk of cracking during processing of the steel sheet. Therefore, the N content is set to 0.0100% or less. The upper limit of the N content is preferably 0.0060% or less. It is difficult to reduce the N content to 0% in industrial production.
[0034] (O:0.0030% or less) O is an impurity element that is inevitably contained in steel. If the O content is excessive, there is a risk of cracking during processing of the steel sheet. Therefore, the O content is set to 0.0030% or less. The upper limit of the O content is preferably 0.0020% or less. It is difficult to reduce the O content to 0% in industrial production.
[0035] (arbitrary element) The base steel sheet of the high-strength galvannealed steel sheet according to this embodiment may contain Ca in the ranges shown below, as necessary. The base steel sheet may also contain one or more elements selected from the group consisting of Nb, V, Cu, Ni, Mg, and rare earth elements (REM) in the ranges shown below, together with Ca or without Ca. By containing these elements alone or in appropriate combination, the properties of the base steel sheet are improved according to the elements contained.
[0036] (Ca: more than 0%, less than 0.0040%) Ca is an element effective in spheroidizing sulfides in steel and improving the bendability of steel sheet. This effect is exhibited when the Ca content exceeds 0%, and increases as the Ca content increases. In order to exhibit this effect more effectively, the lower limit of the Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more. However, if the Ca content is excessive, the effect becomes saturated and the cost increases. Therefore, the upper limit of the Ca content is preferably 0.0040% or less, and more preferably 0.0030% or less.
[0037] (Nb: more than 0%, less than 0.020%) Nb is an element that contributes to increasing the strength of steel sheets. This effect is exhibited if the Nb content exceeds 0%, and increases as the Nb content increases. In order to effectively exhibit this effect, the lower limit of the Nb content is preferably 0.003% or more, and more preferably 0.005% or more. However, if the Nb content is excessive, the hardenability of the steel sheet is deteriorated. Therefore, the upper limit of the Nb content is preferably 0.020% or less, more preferably 0.018% or less, and even more preferably 0.015% or less.
[0038] (V: more than 0%, less than 0.30%) V is an element that contributes to increasing the strength of steel sheets. This effect is exhibited when the V content exceeds 0%, and increases as the V content increases. In order to effectively exhibit this effect, the lower limit of the V content is preferably 0.005% or more, and more preferably 0.010% or more. However, if the V content is excessive, the effect saturates and the cost increases. Therefore, the upper limit of the V content is preferably 0.30% or less, more preferably 0.25% or less, and even more preferably 0.20% or less.
[0039] (Cu: more than 0%, less than 0.30%) Cu is an element effective in improving the corrosion resistance of steel sheets. This effect is exhibited when the Cu content exceeds 0%, and increases as the Cu content increases. In order to effectively exhibit this effect, the lower limit of the Cu content is preferably 0.01% or more, and more preferably 0.05% or more. However, if the Cu content is excessive, the effect saturates and the cost increases. Therefore, the upper limit of the Cu content is preferably 0.30% or less, more preferably 0.20% or less, and even more preferably 0.15% or less.
[0040] (Ni: more than 0%, less than 0.30%) Ni is an element effective in improving the corrosion resistance of steel sheets. This effect is exhibited when the Ni content exceeds 0%, and increases as the Ni content increases. In order to effectively exhibit this effect, the lower limit of the Ni content is preferably 0.03% or more, and more preferably 0.05% or more. However, if the Ni content becomes excessive, the effect saturates and the cost increases. Therefore, the upper limit of the Ni content is preferably 0.30% or less, more preferably 0.20% or less, and even more preferably 0.15% or less.
[0041] (Mg: more than 0%, less than 0.0100%) Mg is an element that contributes to improving the formability of steel sheet. This effect is exhibited if the Mg content is more than 0%. However, if the Mg content is excessive, the pickling property, weldability, hot workability, and economical efficiency of the steel sheet are deteriorated. Therefore, the upper limit of the Mg content is preferably 0.0100% or less, and more preferably 0.0040% or less.
[0042] (REM: more than 0%, less than 0.010%) REM is an element that contributes to improving the formability of steel sheet. This effect is exhibited if the REM content is more than 0%. However, if the REM content is excessive, the pickling property, weldability, hot workability, and economical efficiency of the steel sheet are deteriorated. Therefore, the upper limit of the REM content is preferably 0.010% or less, and more preferably 0.0040% or less.
[0043] (Metal structure of base steel sheet) The metal structure of the base steel sheet of the high-strength galvannealed steel sheet according to this embodiment is 82 volume % or more of martensite (including tempered martensite and self-tempered martensite), 13 volume % or less of bainite, and 5 volume % or less of retained austenite. This allows the high-strength galvannealed steel sheet according to this embodiment to have the specified tensile strength and yield strength. The proportion of each metal structure can be measured by the method described in the examples below.
[0044] (Martensite: 82% by volume or more) The martensite in the metal structure is the base structure of the base steel sheet according to this embodiment. By making the martensite 82 volume % or more of the entire metal structure of the base steel sheet, the yield strength and tensile strength of the steel sheet are increased. If the martensite is less than 82 volume %, other soft structures start to undergo plastic deformation at low stress, and the yield strength and tensile strength of the steel sheet are reduced. The volume fraction of martensite is more preferably 83 volume % or more. There is no upper limit to the volume fraction of martensite, and it may be 100%. The martensite of this embodiment includes not only as-quenched martensite, but also tempered martensite and self-tempered martensite (autotempered martensite).
[0045] (Ferrite, pearlite and bainite: 13% or less by volume in total) Ferrite, pearlite, and bainite are softer than martensite, which is the base structure of the base steel sheet. If these structures increase in the steel sheet, they will begin to plastically deform at low stress, reducing the yield strength and tensile strength of the steel sheet. From this perspective, the total content of ferrite, pearlite, and bainite is set to 13 volume% or less of the entire metal structure of the base steel sheet. There is no lower limit to the volume fraction of ferrite, pearlite, and bainite, and it may be 0 volume%. Hereinafter, ferrite, pearlite, and bainite are collectively referred to as "bainite, etc."
[0046] (Residual austenite: 5% or less by volume) The amount of retained austenite in the metal structure is set to 5% by volume or less relative to the entire metal structure of the base steel sheet. Of the retained austenite, a small amount of film-like retained austenite present at the boundaries of martensite laths has the effect of suppressing the movement of dislocations when stress is applied to the steel sheet, thereby increasing the tensile strength and yield strength. However, the retained austenite itself is softer than the martensite structure. Therefore, if there is an excessive amount of retained austenite, even if it is in the form of a film, both the yield strength and tensile strength of the steel sheet will decrease. From this perspective, the amount of retained austenite is set to 5% by volume or less. The amount of retained austenite may be 0% by volume.
[0047] As will be described in the Examples below, the proportion of retained austenite can be measured by chemically or electrolytically polishing the ground surface of a test piece cut out from a base steel sheet and applying an X-ray diffraction method to the ground surface after polishing. As a method for polishing the ground surface, electrolytic polishing is preferable to chemical polishing from the viewpoint of reducing the burden on the environment.
[0048] (The number of laths in a total length of 300 μm measured by the cutting method is 200 or more.) In order to satisfy high tensile strength and high yield strength, the base steel sheet of the high-strength galvannealed steel sheet according to this embodiment has a number of laths in a total length of 300 μm measured by a cut-away method in an image of the metal structure of the base steel sheet observed with a scanning electron microscope (hereinafter, simply referred to as "number of laths in a total length of 300 μm") of 200 or more. If the number of laths in a total length of 300 μm is less than 200, at least one of the yield strength and tensile strength decreases. The number of laths in a total length of 300 μm is preferably 210 or more, and more preferably 220 or more.
[0049] The "lath" referred to here is a substructure of martensite, a crystal that extends long in one direction. The structure of martensite is layered, as explained below. Martensite is formed by the transformation of quenched austenite. Within one prior austenite grain, there are multiple packets, which are collections of grains with the same crystal habit plane. Within each packet, there are blocks, which are parallel band-like regions. Furthermore, each block contains a collection of laths that have approximately the same crystal orientation and contain a high density of dislocations.
[0050] The "number of laths in a total length of 300 μm measured by the cutting method" as defined in the present invention is measured at 1 / 4 of the plate thickness of a cross section parallel to the rolling direction of the steel plate. Specifically, the cross section of the polished steel plate is corroded with nital, and the cross section is photographed at a magnification of 3000 times using a FE-SEM (Field Emission Scanning Electron Microscope). The number of laths is measured by applying the cutting method to this photograph. The cutting method in this embodiment is a method in which a line (a straight or arc test line) with a total length of 300 μm is drawn on the photographed FE-SEM image, and the number of laths intersecting the test line is determined. The method for measuring the number of laths by the cutting method will be described in more detail in the examples below.
[0051] (Plating layer) The plating layer is a hot-dip galvanized layer formed on the surface of the base steel sheet and then subjected to an alloying treatment, which will be described later. Any hot-dip galvanized layer that is commonly used can be used, and is not particularly limited.
[0052] (Method of manufacturing high-strength galvannealed steel sheet) A method for producing a high-strength galvannealed steel sheet according to this embodiment will be described.
[0053] The high-strength galvannealed steel sheet according to this embodiment that satisfies the above requirements is obtained by hot rolling a slab having the composition of the above-mentioned base steel sheet, coiling it at a predetermined temperature, unwinding the coiled hot-rolled steel sheet and cold rolling it, annealing the cold-rolled steel sheet obtained by cold rolling, cooling the annealed cold-rolled steel sheet to obtain a base steel sheet, hot-dip galvanizing the hot-dip galvanized steel sheet obtained by hot-dip galvanizing, alloying the hot-dip galvanized steel sheet obtained by hot-dip galvanizing, and then cooling it. Each step will be described below.
[0054] (Hot rolling process) The hot rolling conditions are, for example, as follows. In the hot rolling process, a slab having the above-mentioned composition of the steel plate is hot rolled. If the heating temperature of the slab before hot rolling is low, carbides such as TiC may be difficult to dissolve in austenite. Therefore, the heating temperature of the slab before hot rolling is preferably 1100°C or higher. The heating temperature of the slab before hot rolling is more preferably 1200°C or higher. However, if the heating temperature before hot rolling is too high, the cost increases. Therefore, the upper limit of the heating temperature before hot rolling is preferably 1350°C or lower, more preferably 1300°C or lower.
[0055] If the finish rolling temperature of the hot rolling is low, the deformation resistance of the slab during rolling may increase, which may make operation difficult. Therefore, the finish rolling temperature is preferably 850°C or higher, and more preferably 870°C or higher. However, if the finish rolling temperature is too high, the strength of the hot-rolled steel sheet may become excessively high. Therefore, the finish rolling temperature is preferably 980°C or lower, and more preferably 950°C or lower.
[0056] The average cooling rate of the hot-rolled steel sheet obtained by hot rolling from finish rolling to coiling is preferably 10°C / s or more, more preferably 20°C / s or more, in consideration of productivity. On the other hand, if the average cooling rate is too fast, the equipment cost increases. Therefore, the average cooling rate is preferably 100°C / s or less, more preferably 50°C / s or less.
[0057] (Hot-rolled steel sheet winding process) The hot-rolled steel sheet obtained by hot rolling is coiled at 620°C or higher. If the coiling temperature of the hot-rolled steel sheet is less than 620°C, the strength of the hot-rolled steel sheet becomes too high, making cold rolling difficult. The coiling temperature of the hot-rolled steel sheet is preferably 630°C or higher, more preferably 640°C or higher. On the other hand, if the coiling temperature of the hot-rolled steel sheet becomes too high, pickling properties for removing scale deteriorate. Therefore, the coiling temperature is preferably 800°C or lower, more preferably 750°C or lower.
[0058] (Cold rolling process) The coiled hot-rolled steel sheet is unwound and then subjected to cold rolling. The unwound hot-rolled steel sheet is pickled to remove scale, if necessary.
[0059] The lower limit of the rolling ratio during cold rolling is preferably 10% or more. The rolling ratio in this embodiment is synonymous with the "rolling reduction ratio". Specifically, when the thickness of the steel sheet before rolling is h1 and the thickness of the steel sheet after rolling is h2, the rolling ratio (%) is "(h1-h2) / h1×100". When the rolling ratio during cold rolling is less than 10%, the thickness of the hot-rolled steel sheet must be thinned in the hot rolling process to obtain a steel sheet of a predetermined thickness. When the hot-rolled steel sheet is thinned, the length of the hot-rolled steel sheet increases, so that pickling takes time and productivity decreases. The lower limit of the rolling ratio during cold rolling is more preferably 25% or more.
[0060] On the other hand, if the reduction ratio during cold rolling exceeds 70%, a cold rolling mill with high capacity is required, so the upper limit of the reduction ratio during cold rolling is preferably 70% or less, and more preferably 65% or less.
[0061] Fig. 1 is a schematic diagram of a heat pattern of a steel sheet after cold rolling according to the present embodiment. The heat pattern shown in Fig. 1 includes (a) a soaking step, (b) a first cooling step, (c) a second cooling step, (d) an alloying step, (e) a third cooling step, and (f) a fourth cooling step. In order to obtain a high-strength galvannealed steel sheet according to the present embodiment, it is important to appropriately adjust the conditions of each step, particularly (a) to (e), among the steps included in the heat pattern after cold rolling.
[0062] (a) Soaking process In the soaking process, the cold-rolled steel sheet is heated and held at a temperature range of the Ac3 point or higher for 11s or more. If the heating temperature is lower than the Ac3 point, there is a possibility that soft ferrite that reduces the yield strength and tensile strength of the steel sheet may remain. Therefore, the lower limit of the holding temperature in the soaking process is set to the Ac3 point. The lower limit of the holding temperature in the soaking process is preferably (Ac3 point + 5) ° C. In addition, the holding temperature in the soaking process may be lower than the solidus temperature of the cold-rolled steel sheet, and there is no particular upper limit. However, if the holding temperature in the soaking process is too high, productivity will deteriorate, or the economic efficiency will deteriorate due to increased fuel consumption of the furnace. Therefore, the upper limit of the holding temperature in the soaking process is preferably 980 ° C. or lower. In the soaking process, the temperature of the cold-rolled steel sheet may be kept constant, or the temperature of the cold-rolled steel sheet may fluctuate as long as it is within the above holding temperature range.
[0063] In addition, if the holding time in the temperature range of the Ac3 point or higher is less than 11 s, the amount of elements dissolved in the steel sheet during the soaking process from the carbides present in the cold-rolled steel sheet before heating and the elements dissolved in the carbides will be insufficient, and the hardenability will deteriorate. Therefore, the holding time in the temperature range of the Ac3 point or higher is set to 11 s or more. The lower limit of the holding time in the temperature range of the Ac3 point or higher is preferably 12 s or more, more preferably 15 s. There is no particular upper limit for the holding time in the temperature range of the Ac3 point or higher. However, if the holding time is too long, the productivity will deteriorate, so the holding time is preferably less than 600 s.
[0064] The Ac3 point can be calculated by the following formula (2) (William C. (Leslie, "Leslie Steel Materials Science", Maruzen Co., Ltd., p. 273) The [element symbol] in formula (2) represents the content (mass%) of the corresponding element. Ac3(℃)=910-203×[C] 1 / 2 -15.2×[Ni]+44.7×[Si]+104×[V]+31.5×[Mo]+13.1×[W]-{30×[Mn]+11×[Cr]+20×[Cu]-700×[P]-400×[Al]-120×[As]-400×[Ti]} …(2)
[0065] (b) First cooling step In the first cooling step, the cold-rolled steel sheet heated and held in the soaking step at a temperature range of Ac3 point or higher is cooled to a temperature range of 540 to 580°C (first temperature range) at an average cooling rate of 3°C / s or higher. Specifically, after starting cooling in the soaking step, the steel sheet is cooled from the Ac3 point to the first temperature range at an average cooling rate of 3°C / s or higher. If the average cooling rate is less than 3°C / s, the possibility of ferrite being generated increases, making it difficult to ensure the yield strength and tensile strength specified in the present invention. Therefore, the average cooling rate needs to be 3°C / s or higher, preferably 4°C / s or higher, and more preferably 5°C / s or higher. On the other hand, although there is no particular upper limit, if the average cooling rate exceeds 50°C / s, it becomes difficult to control the steel sheet temperature, and the equipment cost increases. Therefore, the upper limit of the average cooling rate is 50°C / s or lower, preferably 40°C / s or lower.
[0066] (c) Second cooling step In the second cooling step, after the first cooling step, the cold-rolled steel sheet is cooled to a temperature range of 410 to 480°C (second temperature range) within 90 seconds to obtain a base steel sheet. More specifically, the cold-rolled steel sheet is cooled from the first temperature range to the second temperature range in a time of 90 seconds or less while maintaining a temperature of the Ms point or higher. If the cooling time from the first temperature range to the second temperature range exceeds 90 seconds, there is a concern that bainite may increase, so the cooling time from the first temperature range to the second temperature range is set to 90 seconds or less. The upper limit of the cooling time from the first temperature range to the second temperature range is preferably 70 seconds or less. The upper limit of the second temperature range is preferably 470°C or less, more preferably 460°C or less.
[0067] In the second cooling step, it is preferable to keep the cold-rolled steel sheet at a temperature equal to or higher than the Ms point. If the cold-rolled steel sheet is cooled below the Ms point in the second cooling step, martensite will be formed before the subsequent alloying step, and the final structure after the heat treatment will have a reduced lath spacing, resulting in a decrease in tensile strength.
[0068] The "Ms point" is the temperature at which austenite begins to transform into martensite, and can be easily calculated from the chemical composition of the steel plate based on the following formula (3) ("Modern Metal Science Lecture Series, Materials Edition, Vol. 4, Steel Materials," Japan Institute of Metals, June 1985, p. 45). The [element symbol] in formula (3) represents the content (mass%) of the corresponding element in the steel plate, and elements not contained in the steel plate are calculated as 0. Ms point (℃)=550-361×[C]-39×[Mn]-35×[V]-20×[Cr]-17×[Ni]-10×[Cu]-5×([Mo]+[W])+15×[Co]+30×[Al]…(3)
[0069] (d) Alloying process After the second cooling step and prior to the alloying step, the base steel sheet is subjected to hot-dip galvanization. The base steel sheet cooled to the second temperature range is introduced into a plating pot containing a hot-dip galvanizing bath and is subjected to an immersion treatment in the plating bath. Through this immersion treatment, the base steel sheet is subjected to hot-dip galvanization, and a hot-dip galvanized steel sheet is obtained. In the alloying step, the obtained hot-dip galvanized steel sheet is subjected to an alloying treatment.
[0070] In the alloying process, the hot-dip galvanized steel sheet is heated to a temperature range of 550°C or less to perform alloying treatment of hot-dip galvanization. Specifically, the hot-dip galvanized steel sheet is heated to alloy the zinc contained in the hot-dip galvanization with the iron contained in the base steel sheet. If the heating temperature in this alloying process exceeds 550°C, the possibility of ferrite being generated in the base steel sheet increases, and the tensile strength of the alloyed hot-dip galvanized steel sheet may decrease. In addition, the diffusion of iron from the base steel sheet to the zinc of the hot-dip galvanization becomes excessive, and the plating layer is likely to peel off during press forming or the like. The upper limit of the heating temperature in the alloying process is preferably 540°C or less, more preferably 530°C or less. The heating temperature in the alloying process may be higher than the temperature of the hot-dip galvanized steel sheet immediately after immersion in the plating bath, and is preferably 420°C or more, more preferably 430°C or more.
[0071] (e) The third cooling step In the third cooling step, the galvannealed steel sheet obtained in the alloying step is cooled to a temperature range of 230 to 340°C (third temperature range) at an average cooling rate of 5.0°C / s or more. More specifically, the steel sheet is cooled from immediately after the alloying step to a cooling stop temperature in the third temperature range at an average cooling rate of 5.0°C / s or more. In this way, the high-strength galvannealed steel sheet according to the above-mentioned embodiment can be obtained. If the average cooling rate in the third cooling step is less than 5.0°C / s, there is a concern that bainite may increase. Even if the generation of bainite is suppressed, the austenite is stabilized by the advancement of carbon distribution from martensite generated after passing the Ms point to untransformed austenite, and the amount of austenite transformed to martensite decreases. As a result, the steel sheet is likely to contain more than 5% by volume of retained austenite. Therefore, the average cooling rate in the third cooling step is set to 5.0°C / s or more. The average cooling rate in the third cooling step is preferably 8.0°C / s or more, more preferably 10°C / s or more. The upper limit of the average speed is not particularly specified, but since increasing the cooling capacity of the cooling equipment places a large load on the cooling equipment, the speed is preferably 50° C. / s or less, and more preferably 40° C. / s or less.
[0072] (f) The fourth cooling step The third cooling step is followed by a fourth cooling step. In the fourth cooling step, the high-strength galvannealed steel sheet is preferably cooled from the third temperature range to a cooling stop temperature of 50°C or less at an average cooling rate of 5.0°C / s or less. If the average cooling rate in the fourth cooling step exceeds 5.0°C / s, the martensite in the base steel sheet does not undergo self-tempering, and the structure may become brittle. The average cooling rate in the fourth cooling step is more preferably 4.0°C or less. In addition, the productivity of the high-strength galvannealed steel sheet is deteriorated, so the average cooling rate in the fourth cooling step is preferably 0.05°C / s or more, more preferably 0.10°C / s or more.
[0073] In addition, when the cooling stop temperature in the third cooling step is higher than 230° C., the average cooling rate from the cooling stop temperature in the third cooling step to 230° C. is not important. In the fourth cooling step, cooling to room temperature may be performed at any cooling rate as long as heating is not performed after the third cooling step.
[0074] (Other processes) After the fourth cooling step, the high-strength galvannealed steel sheet may be processed or tempered as necessary.
[0075] The high-strength galvannealed steel sheet cooled in the fourth cooling step has sufficiently high tensile strength and yield strength even without temper rolling. However, it is also possible to achieve even higher yield strength by subjecting the plated steel sheet to processing such as temper rolling to cause work hardening. Such improvement in yield strength is due to the reduction in mobile dislocations in martensite of the base steel sheet by processing the plated steel sheet. Mobile dislocations in martensite of the base steel sheet are preferably small because they reduce the yield strength of the plated steel sheet. The upper limit of the processing amount of the plated steel sheet is not particularly specified. However, the plated steel sheet suffers from shape deterioration and strength anisotropy due to processing. Therefore, the upper limit of the processing amount in temper rolling is preferably 5% or less, more preferably 4% or less, in terms of the elongation in the rolling direction of the high-strength galvannealed steel sheet. As processing other than temper rolling, processing using a leveler may be performed. Even in processing using a leveler, the preferred processing amount is the same as that in temper rolling.
[0076] In addition, even if high-strength galvannealed steel sheet is tempered to a moderate extent, it is possible to achieve a higher yield strength while maintaining a high tensile strength, because tempering reduces mobile dislocations in martensite of the base steel sheet, as in the case of processing.
[0077] Although the tempering temperature is not particularly specified, when it exceeds 500°C, excessive tempering occurs, the number of martensite laths in the base steel sheet decreases, and the tensile strength and yield strength of the high-strength galvannealed steel sheet decrease. Therefore, the upper limit of the tempering temperature is preferably 500°C or less.
[0078] The high-strength galvannealed steel sheet of the present invention is not limited to that obtained by the above-mentioned manufacturing method, and may be that obtained by other manufacturing methods as long as the requirements defined in the present invention are satisfied.
[0079] As described above, this specification discloses various aspects of the technology, the main technologies of which are summarized below.
[0080] As described above, a high-strength galvannealed steel sheet according to one aspect of the present invention is a high-strength galvannealed steel sheet having a plating layer on a surface of a base steel sheet, The base steel sheet is composed of: C: 0.19-0.30%, Si: more than 0%, less than 0.70%, Mn: 1.8-3.0%, P: more than 0%, less than 0.020%, S: more than 0%, less than 0.05%, Al: 0.015-0.060%, Cr: 0.05~0.8%, Ti: 0.015 to 0.080%, B: 0.0010~0.0150%, Mo: more than 0%, less than 0.40%, N: 0.0100% or less, and O: 0.0030% or less, and the remainder being iron and unavoidable impurities, The Cr content [Cr] (mass%) and the Si content [Si] (mass%) of the base steel sheet satisfy 2 × [Cr] - [Si] ≧ 0.1, In the metal structure of the base steel sheet, martensite (including tempered martensite and self-tempered martensite) is 82 vol% or more, ferrite, pearlite and bainite are 13 vol% or less, and retained austenite is 5 vol% or less, In an image of the metal structure of the base steel sheet observed with a scanning electron microscope, the number of laths in a total length of 300 μm measured by a cutting method is 200 or more, the yield strength is 970 MPa or more, and the tensile strength is 1470 MPa or more.
[0081] According to this configuration, it is possible to obtain a high-strength galvannealed steel sheet having a yield strength of 970 MPa or more, a tensile strength of 1470 MPa or more, and excellent LME cracking resistance.
[0082] In the high-strength galvannealed steel sheet having the above configuration, the base steel sheet may further contain, by mass%, Ca: more than 0% and 0.0040% or less.
[0083] According to this configuration, a high-strength galvannealed steel sheet also having excellent bendability can be obtained.
[0084] In the high-strength galvannealed steel sheet having the above configuration, the base steel sheet further comprises, in mass%, Nb: more than 0%, less than 0.020%, V: more than 0%, less than 0.30%, Cu: more than 0%, less than 0.30%, Ni: more than 0%, less than 0.30%, Mg: More than 0%, 0.0100% or less, and REM: more than 0%, less than 0.010%, may contain one or more selected from the group consisting of:
[0085] According to this configuration, a high-strength galvannealed steel sheet having even greater strength, corrosion resistance, or formability can be obtained.
[0086] A method for producing a high-strength galvannealed steel sheet according to another aspect of the present invention includes hot rolling a slab having the above composition, The hot-rolled steel sheet obtained by hot rolling is coiled at 620°C or higher, The coiled hot-rolled steel sheet is unwound and cold-rolled; The cold-rolled steel sheet obtained by cold rolling is heated and held in a temperature range of Ac3 point or higher for 11 s or more, and the heated and held cold-rolled steel sheet is cooled to a temperature range of 540 to 580 ° C. at an average cooling rate of 3 ° C. / s or more, and further cooled to a temperature range of 410 to 480 ° C. within 90 s, The cold-rolled steel sheet is cooled to obtain a base steel sheet, which is then subjected to hot-dip galvanizing. The hot-dip galvanized steel sheet obtained by hot-dip galvanizing is heated to a temperature range of 550°C or less to perform an alloying treatment of the hot-dip galvanizing, The method includes cooling the galvannealed steel sheet obtained by subjecting the hot-dip galvannealed steel sheet to an alloying treatment to a temperature range of 230 to 340° C. at an average cooling rate of 5° C. / s or more.
[0087] According to this configuration, it is possible to produce a high-strength galvannealed steel sheet having a yield strength of 970 MPa or more, a tensile strength of 1470 MPa or more, and excellent LME cracking resistance.
[0088] In the method for producing a high strength steel sheet having the above configuration, the cooled galvannealed steel sheet may be worked at an elongation rate of 5% or less.
[0089] According to this configuration, a high-strength galvannealed steel sheet having even more excellent yield strength can be manufactured.
[0090] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and may be modified within the scope of the above and below-described aims, and all such modifications are included in the technical scope of the present invention. EXAMPLES
[0091] (Manufacturing method) Molten steel was cast to produce slabs with the chemical composition shown in Table 1 (steel types: A, B, C, D, E, F, G, H, I, J). In Table 1, values marked with "<" mean that the value was below the measurement limit. P, S, N, and O are unavoidable impurities as described above, and the values shown in the P, S, N, and O columns mean the amounts that were unavoidably included. The remainder of the chemical composition shown in Table 1 is iron and unavoidable impurities other than P, S, N, and O.
[0092] The Ac3 and Ms points of each steel type are also shown in Table 1. The Ac3 point was calculated using the above formula (2), and the Ms point was calculated using the above formula (3). When calculating the Ac3 and Ms points, the contents of elements that were not added and elements whose contents were below the measurement limit were set to 0.
[0093] Table 1 also shows the "2 x [Cr] - [Si]" value (referred to as "CS value" in Table 1) for each steel type. Here, [Cr] and [Si] are the contents (mass%) of the corresponding elements in the slab. When the CS value is 0.1 or more, the following formula (1) is satisfied. 2 × [Cr]-[Si]≧0.1 … (1)
[0094] [Table 1]
[0095] The slabs of steel grades A to F and H to J were heated to a temperature range of 1250°C, and the slab of steel grade G was heated to a temperature range of 1265 to 1275°C, and hot rolled to a thickness range of 2.0 to 3.0 mm to obtain hot rolled steel sheets. The temperature of the hot rolled steel sheet at the completion of finish rolling was 900°C for steel grades A to F and H to J, and 920°C for steel grade G. The average cooling rate of the hot rolled steel sheet from the completion of finish rolling to the start of coiling of the hot rolled steel sheet was 10 to 30°C / s. The coiling start temperature of the hot rolled steel sheet was 650°C for steel grades A to F, and 680°C for steel grades G to J, and coiling of the hot rolled steel sheet and treatment equivalent to coiling were performed.
[0096] The obtained hot-rolled steel sheets were pickled, and then surface grinding and cold rolling were combined to obtain cold-rolled steel sheets with a thickness of 1.4 to 1.6 mm. The cold rolling ratio (rolling ratio during cold rolling) of each steel type was in the range of 10 to 60%. The obtained cold-rolled steel sheets of steel types A to J were subjected to heat treatment Nos. 1 to 14 shown in Table 2 to produce steel sheets (steel sheets or galvannealed steel sheets) of experiments Nos. 1 to 18. In heat treatments Nos. 1 to 7, 13, and 14, a laboratory simulator was used as a heat treatment furnace, and in heat treatments Nos. 8 to 12, actual equipment was used. In experiment No. 11, the "time from Ac3 point to maximum temperature reached" in the soaking process (process (a) shown in FIG. 1) was 10 s, and the "holding time in the temperature range above Ac3 point", which is the sum of the "time from the maximum temperature reached to the start of cooling until the Ac3 point" to this time, was less than 11 s.
[0097] [Table 2]
[0098] In heat treatments Nos. 1 to 7, 13, and 14, the steel sheets were not subjected to hot-dip galvanizing and alloying treatments after the second cooling step (step (c) shown in FIG. 1). In heat treatments Nos. 8 to 12, the steel sheets were subjected to hot-dip galvanizing and alloying treatments (step (d) shown in FIG. 1) after the second cooling step.
[0099] For the steel sheets that underwent heat treatments No. 1 to 7, 13, and 14, the structure was observed and the mechanical properties were evaluated after heat treatments simulating hot-dip galvanizing and alloying treatments (step (d) shown in Figure 1). For the steel sheets that underwent heat treatments No. 8 to 12, the structure was observed and the mechanical properties were evaluated after plating or the specified work hardening treatment (temper rolling).
[0100] The steel sheets that underwent heat treatments Nos. 1 to 7, 13, and 14 were subjected to observation of the structure and evaluation of the mechanical properties after heat treatments simulating the hot-dip galvanizing and alloying treatments. This is because the strength of the steel sheet is not significantly affected by the presence or absence of plating, whereas the strength of the steel sheet is significantly affected by heat treatment.
[0101] (Structural observation and evaluation of mechanical properties) For each of the steel plates obtained in this way, the volume fraction of martensite, bainite, and retained austenite, the number of laths in a total length of 300 μm measured by the cutting method, and the mechanical properties (0.2% yield strength σ 0.2 and tensile strength (TS) were measured according to the following procedure.
[0102] (Volume ratio of each tissue) According to the manufacturing method of this example, the possibility of the presence of structures other than martensite, bainite, and retained austenite (for example, ferrite and pearlite) in each steel sheet is extremely low. Therefore, structures other than martensite, bainite, and retained austenite were not measured. Below, the method of measuring the volume fraction of each structure will be described in the order of retained austenite, bainite, and martensite.
[0103] (volume fraction of retained austenite) The volume fraction of retained austenite was measured as follows. Test pieces were cut out to a size of 20 mm x 20 mm from heat-treated steel sheets (thickness 1.4 to 1.6 mm). The test pieces were ground from the surface to 1 / 4 of the plate thickness, and the ground surface was polished by chemical polishing (Experiment No. 8) or electrolytic polishing (Experiment Nos. 16 to 18). The volume fraction of retained austenite was measured for the ground surface after polishing by X-ray diffraction (ISIJ Int. Vol. 33. (1993), No. 7, P. 776). A two-dimensional micro X-ray diffraction device (Rigaku Corporation, RINT-RAPID II) was used for the measurement. Co was used as the target.
[0104] However, for some test pieces, the volume fraction of retained austenite was assumed to be 5% or less based on the C or Si content, or the heat treatment conditions under the third or fourth cooling conditions. Therefore, the volume fraction of retained austenite was not measured by X-ray diffraction method for such test pieces. For the steel plates (Tests Nos. 1 to 7, 9 to 15) for which the volume fraction of retained austenite was not measured, the maximum value of 5% was used as the assumed value for the volume fraction of retained austenite.
[0105] (Volume fraction of bainite and martensite) The volume fractions of bainite and martensite were measured and calculated by the following procedure. Test pieces were cut out to a size of 20 mm x 20 mm from heat-treated steel sheets (thickness 1.4 to 1.6 mm). The cross section of the test pieces parallel to the rolling direction was polished, and the polished surface was etched with nital. A photograph (magnification 3000 times) of the structure of 1 / 4 of the plate thickness of the polished surface that had been etched with nital was taken using an FE-SEM. The structure was classified as bainite or martensite based on the color of the grains in the structure photograph, and the area fractions of bainite and martensite were measured by the point counting method. Specifically, an orthogonal grid was set at 3 μm intervals (9 mm intervals on the photograph) on the FE-SEM image, and the structure at the points where the grids intersect at right angles (grid points) was classified as bainite or martensite. The structure was classified for 100 grid points, and the area fractions of bainite and martensite were calculated using the results. Measurements were performed on one field of view (one photograph) for each test piece.
[0106] Figure 2 is an example of a scanning electron microscope photograph at a magnification of 3000 times showing the structure of a quarter of the plate thickness of a cross section parallel to the rolling direction of a test piece, the polished surface that was etched with nital. In Figure 2, the structure that appears black is bainite, and the remaining part is martensite.
[0107] As can be seen from the above explanation, in this embodiment, the volume fraction of retained austenite and the area fractions of bainite and martensite are measured by different methods, so the total of the proportions of each structure does not necessarily equal 100%.
[0108] Therefore, in this embodiment, when determining the volume fraction of bainite and the volume fraction of martensite, the total of the volume fractions of the retained austenite, bainite, and martensite was adjusted to be 100 volume%. Specifically, the volume fraction of the retained austenite measured by the X-ray diffraction method (or the assumed value of the volume fraction of the retained austenite) was subtracted from 100 volume%, and this value was considered as the total volume fraction of bainite and martensite. This total volume fraction of bainite and martensite was proportionally allocated using the area fractions of bainite and martensite measured by the point counting method, and each volume fraction of bainite and martensite was determined. The volume fractions of each structure obtained in this way are shown in Table 3.
[0109] [Table 3]
[0110] (Number of laths in a total length of 300 μm) The number of laths in a total length of 300 μm was measured by the intercept method. The intercept method is a method for measuring ordinary particle size (JIS G 0551:2013). In this example, the intercept method was applied as a method for measuring the number of laths.
[0111] The number of laths was measured at 1 / 4 of the plate thickness of a cross section parallel to the rolling direction of the steel plate. The cross section of the steel plate was polished, corroded with nital, and photographed at 3000 times magnification using an FE-SEM. In the photographed FE-SEM image, the region that was white and had a longest length of 1 μm or more was determined as a lath. Figure 3 is a schematic diagram of the state in which the number of laths was measured by the cutting method. A line (test line) with a total length of 300 μm was drawn on the photographed FE-SEM image, and the number of times the line passed through the lath (the number of laths intersecting with the test line) was measured as shown in Figure 3. The number of laths intersecting with the test line with a total length of 300 μm is called the "number of laths in a total length of 300 μm." The measured number of laths in a total length of 300 μm is shown in Table 3.
[0112] (Mechanical property evaluation) The mechanical properties of the heat-treated steel sheets are tensile strength TS and 0.2% yield strength σ 0.2 The tensile strength TS and 0.2% yield strength σ 0.2 was measured using a JIS No. 5 test piece (plate-shaped test piece) taken so that the direction perpendicular to the rolling direction of cold rolling was the longitudinal direction of the test piece. The measurement conditions for Experiments No. 11 to 15 were based on JIS Z 2241:2011. The measurement conditions for Experiments No. 1 to 10 and 16 to 18 were based on JIS Z 2241:2011, except that the crosshead displacement speed was kept constant at 10 mm / min. The measured tensile strength TS and 0.2% proof stress σ 0.2 The results are shown in Table 3. The tensile strength TS is 1470 MPa or more and the 0.2% yield strength σ 0.2 If the strength was 970 MPa or more, the mechanical properties were deemed to be acceptable.
[0113] (Evaluation of LME crack resistance) The LME cracking resistance is greatly affected by the chemical composition of the steel sheet, and the effect of heat treatment is smaller than that of the chemical composition. Therefore, the LME cracking resistance can be evaluated by the chemical composition. In this example, the LME cracking resistance of each steel sheet was evaluated by the following method.
[0114] For cold-rolled steel sheets of steel types A to F, the amount of zinc coating is 50 g / m 2 The obtained galvanized steel sheets were heated to 350°C and subjected to alloying treatment of galvanization. The obtained alloyed galvanized steel sheets were each cut to obtain two samples of 140 mm × 35 mm each.
[0115] Figure 4 is a front view of a sample for evaluating LME cracking resistance. As shown in Figure 4, a mild steel plate 2 was sandwiched between two samples 1 taken to form a plate assembly, and both ends of this three-plate assembly were fixed with clamps. Below, the two samples 1 are also referred to as the upper plate and the lower plate, respectively. Resistance spot welding was performed at the center of the fixed three-plate assembly to prepare a sample for evaluating LME cracking resistance. The mild steel plate 2 had a tensile strength of 270 MPa and a coating weight of 55 g / m on one side. 2A GA steel sheet (galvannealed steel sheet) with dimensions of 0.75 mm × 140 mm × 35 mm was used. One sample for evaluating LME crack resistance was prepared for each of the steel types A to J. The welding conditions were as follows:
[0116] Welding machine: AC inverter resistance welding machine Electrodes: Upper and lower DR type Cu-Cr (dome radius) Electrode striking angle: 5° Electrode diameter: tip diameter 8mm Cooling water flow rate: Approximately 2L / min up and down Pressure: 350kgf Initialization pressure time: 60 cycles / 60Hz Uplobe: 1 cycle / 60Hz First stage of energization Current value: 7.2kA Time (cycles / 60Hz): 8 Second stage of power supply Current value: 9kA Time (cycles / 60Hz): 17 Down lobe (cycles / 60Hz): 30 Hold time (cycles / 60Hz): 5
[0117] (LME crack observation method) From the LME crack resistance evaluation samples thus prepared, samples for LME crack observation were prepared. The LME crack observation samples were prepared so that the observation surface was a cross section passing through the diameter of the weld nugget. The surface layers of the upper and lower plates of the LME crack observation samples were observed using an optical microscope at 25 to 100 magnifications to investigate the presence or absence of cracks. Figure 5 is an example of an optical microscope photograph of the LME crack observation sample. As shown in Figure 5, cracks of 50 μm or more in length were judged to be LME cracks in the weld. The results of the observation of the LME crack resistance evaluation samples for each steel type are shown in Table 4, with those with cracks rated as × (not acceptable) and those without cracks rated as ◯ (good). The evaluation result for steel type G is an estimate.
[0118] [Table 4]
[0119] (Evaluation Results) (mechanical properties) From the results shown in Table 2, the following can be considered. Experiments Nos. 2 to 4, 8 to 10, and 12 to 18 are examples in which steel sheets were manufactured under appropriate heat treatment conditions using steel types (steel types B, C, F to J) that satisfy the chemical composition specified in the present invention. In the steel sheets of these examples, the ratio of each structure in the metal structure and the number of laths in a total length of 300 μm were appropriately adjusted, and the tensile strength TS was 1470 MPa or more and the 0.2% proof stress σ 0.2 The mechanical properties were found to be above 970 MPa, which satisfied the pass criteria.
[0120] In contrast, Test Nos. 1, 5, 6, and 11 are comparative examples that do not satisfy any of the requirements stipulated in the present invention. The steel sheets of these comparative examples did not satisfy the pass criteria for mechanical properties.
[0121] Experiments Nos. 5 and 11 are examples in which the number of laths per total length of 300 μm specified in the present invention was not satisfied.
[0122] The steel plate of Experiment No. 5 reached a low temperature of 150°C in the first cooling step (b), and although the metal structure satisfied the requirements of the present invention, it did not satisfy the number of laths per total length of 300 μm specified in the present invention. Therefore, the tensile strength TS was low and the mechanical properties did not satisfy the pass criteria.
[0123] In the steel plate of Experiment No. 11, the holding time in the temperature range above the Ac3 point in the soaking process (a) was less than 11 s, the number of laths in a total length of 300 μm was less than the stipulated in the present invention, and the volume fraction of bainite, etc. was higher than the stipulated in the present invention. Therefore, the tensile strength TS and 0.2% proof stress σ 0.2 The mechanical properties were low and did not meet the acceptance criteria.
[0124] Experiments Nos. 1 and 6 are examples in which steel types (steel types A and D in Table 1) that do not satisfy the chemical composition specified in the present invention were used.
[0125] In the steel plate of Experiment No. 1, the Cr content of steel type A was less than the amount specified in the present invention, the CS value was less than 0.1, and the formula (1) was not satisfied. As a result, the hardenability was insufficient, and the volume fraction of bainite, etc. was higher than the amount specified in the present invention. Therefore, the tensile strength TS and 0.2% proof stress σ 0.2 The mechanical properties were low and did not meet the acceptance criteria.
[0126] The steel plate of Experiment No. 6 had a Si content of steel type D greater than the amount specified in the present invention, and a CS value of less than 0.1, and did not satisfy formula (1). This resulted in insufficient hardenability and a higher volume fraction of bainite, etc., than specified in the present invention. As a result, the tensile strength TS and 0.2% proof stress σ 0.2 The mechanical properties were low and did not meet the acceptance criteria.
[0127] The steel plate of Test No. 7 is a comparative example that uses a steel type (steel type E in Table 1) that does not satisfy the chemical composition specified in the present invention, but it satisfied the pass criteria for mechanical properties.
[0128] (LME crack resistance) As shown in Table 4, the steel sheets of the steel types (steel types B, C, F to J) that satisfy the chemical composition specified in the present invention had excellent LME cracking resistance. Therefore, it is considered that the steel sheets of Experiments Nos. 2 to 4, 8 to 10, and 12 to 18 using steel types B, C, F to J also had excellent LME cracking resistance.
[0129] On the other hand, the steel sheets of steel type A, which had a CS value of less than 0.1 and did not satisfy formula (1), steel type D, which had a Si content greater than the amount specified in the present invention and did not satisfy formula (1), and steel type E, which had a Si content greater than the amount specified in the present invention, were poor in LME cracking resistance. Therefore, it is believed that the steel sheets of Experiments Nos. 1, 6, and 7, which used steel types A, D, and E, were also poor in LME cracking resistance. [Explanation of symbols]
[0130] 1. Sample 2 Mild steel plate
Claims
1. A high-strength galvannealed steel sheet having a plating layer on a surface of a base steel sheet, The base steel sheet is composed of: C: 0.19-0.30%, Si: more than 0%, 0.70% or less, Mn: 1.8-3.0%, P: more than 0%, less than 0.020%, S: more than 0%, less than 0.05%, Al: 0.015-0.060%, Cr: 0.05-0.8%, Ti: 0.015-0.080%, B: 0.0010 to 0.0150%, Mo: more than 0%, less than 0.40%, N: 0.0100% or less, and O: 0.0030% or less, and the remainder being iron and unavoidable impurities, The Cr content [Cr] (mass%) and the Si content [Si] (mass%) of the base steel sheet satisfy 2 × [Cr] - [Si] ≧ 0.1, In the metal structure of the base steel sheet, martensite (including tempered martensite and self-tempered martensite) is 82 vol% or more, ferrite, pearlite and bainite are 13 vol% or less, and retained austenite is 5 vol% or less, A high-strength galvannealed steel sheet, in which in an image of the metal structure of the base steel sheet observed with a scanning electron microscope, the number of laths within a total length of 300 μm measured by a cutting method is 200 or more, the yield strength is 970 MPa or more, and the tensile strength is 1470 MPa or more.
2. The base steel sheet further comprises, in mass%, Ca: more than 0%, less than 0.0040%, The high-strength galvannealed steel sheet according to claim 1, comprising:
3. The base steel sheet further comprises, in mass%, Nb: more than 0%, less than 0.020%, V: more than 0%, less than 0.30%, Cu: more than 0%, 0.30% or less, Ni: more than 0%, less than 0.30%, Mg: more than 0% and 0.0100% or less, and REM: more than 0%, less than 0.010%, The high-strength galvannealed steel sheet according to claim 1 or 2, comprising one or more selected from the group consisting of:
4. A method for producing a high-strength galvannealed steel sheet according to any one of claims 1 to 3, comprising the steps of: A slab having a composition defined in any one of claims 1 to 3 is hot rolled, The hot-rolled steel sheet obtained by hot rolling is coiled at 620°C or higher, The coiled hot-rolled steel sheet is unwound and cold-rolled; The cold-rolled steel sheet obtained by cold rolling is heated and held in a temperature range of Ac3 point or higher for 11 s or more, and the heated and held cold-rolled steel sheet is cooled to a temperature range of 540 to 580 ° C. at an average cooling rate of 3 ° C. / s or more, and further cooled to a temperature range of 410 to 480 ° C. within 90 s, The cold-rolled steel sheet is cooled to obtain a base steel sheet, which is then subjected to hot-dip galvanizing. The hot-dip galvanized steel sheet obtained by hot-dip galvanization is heated to a temperature range of 550°C or less to perform an alloying treatment of the hot-dip galvanization, and cooling the galvannealed steel sheet obtained by subjecting the hot-dip galvannealed steel sheet to an alloying treatment to a temperature range of 230 to 340°C at an average cooling rate of 5°C / s or more.
5. The method for producing a high-strength galvannealed steel sheet according to claim 4, wherein the cooled galvannealed steel sheet is worked to an elongation of 5% or less.
Citation Information
Patent Citations
Tool steel
JP1978065216A
High strength steel sheet and high strength galvanized steel sheet
JP2019173156A
Resistance spot welding method for galvanized high-tensile steel with good joint performance
JP2019536631A
High strength steel plate and method for manufacturing the same
JP6787535B1
High-strength steel plate and high-strength zinc-plated steel plate
WO2019188190A1